Futebol, tecnologia e aprendizagem: corpo, performance e criatividade - Ferreira, Almir de Oliveira (2010)
This work takes as its object of study the processes of teaching and learning soccer in professional teams and schools, and the increasing role played by the use of technology in the development of professional soccer athletes. The research takes in account the history and evolution of this sport, its ancient and modern forms, up to its recent up-grade as a popular spectacle that raises emotions and moves masses in different contexts and countries around the globe, with enormous presence in Brazilian culture. Designing a broad picture of the strategies of athlete's preparation in such context, and considering the impact of scientific thinking and technology upon the soccer player's perfomance, the research takes advantage of directions offered by Merleau-Pontyan's Fenomenology to propose a way of understanding the ways by which embodiment turns into one's hability of finding creative solution for high-complexity cognitive challenges demanded by a soccer game. Taking also in account the role of electronic games which simulate soccer games, and how such games re-signify soccer's training, we aim to establish such a relation between learning soccer, children's development, ludicity and performance, which favors a superseding of the barriers of representationalism, towards creativity. Through the work, we use as reference, mainly, Merleau-Ponty and his followers; the works of Michael Foucault about body and discipline; accounts of electronic games use by young athletes; and works by Gallahue, Unazelt, and Frisselli & Mantovani